Efeito do óxido nítrico sobre fêmures e vértebras lombares de ratos orquiectomizados - Queiroz, Edvanina de Sousa Costa (Universidade Federal de São Carlos, 2007)
Osteoporosis is attributed to an imbalance between bone formation and resorption, followed by bone mass loss and microarchitectural deterioration, leading to increased bone fragility and fracture risk. Nitric oxide (NO) is a signaling molecule with important regulatory effects on bone cell function. Nitric oxide donor nitroglycerin has been reported to alleviate ovariectomy-induced and corticosteroid-induced bone loss. The aim of the present study was to investigate the effect of NO on cancellous and cortical bone of orchiectomized rats. A total of 98 male Wistar rats (four months old) were randomly divided in the following groups - Experiment I: intact treated with saline (stomacal gavage - gv), orchiectomized treated with saline (gv), and orchiectomized treated with NO donor isosorbide dinitrate - ISDN (gv); Experiment II: intact treated with saline (subcutaneous injection - sc), orchiectomized treated with saline (sc), and orchiectomized treated with NO synthase inhibitor NG-nitro-L-arginine-methylester - L-NAME (sc); Experiment III: intact treated with saline (intraperitoneous injection - ip), orchiectomized treated with saline (ip), and orchiectomized treated with NO precursor L-arginine (ip); Basal group: one group was killed at the beginning of the study (four months old) and served as a baseline group. The animals were killed after 8 weeks of treatment. At death, both femurs and lumbar vertebrae (L5-6) were obtained from each rat, and changes in both cancellous and cortical bone mass and biomechanical competence were assessed. The treatment with NO donor isosorbide dinitrate protected the cortical bone mass of adult rats from the deleterious effects of castration. The protective effect of ISDN treatment on the cancellous bone mass was not as significant as the one observed on the cortical bone. The L-NAME treatment did not increase the deleterious effects induced by orchiectomy in both cancellous and cortical bone mass. No effect was observed with the L-arginine treatment, in the dose used in this study. In conclusion, this study suggest that NO donor isosorbide dinitrate can be used in the future as an alternative pharmacological strategy for the prevention of androgen deficiency osteoporosis, in men with proven hypogonadism and in eugonadal men.
Keywords: Osteoporose; Osteoporose experimental; Doadores de óxido nítrico (NO); Dinitrato de isossorbida (ISDN); Biomecânica óssea; Massa óssea; Osteoporosis; NO donor; ISDN; Biomechanical competence; Bone mass; CIENCIAS BIOLOGICAS::FISIOLOGIA